THE ROLE OF PURA RAHARJA HOSPITAL MANAGEMENT IN SURABAYA IN SUPERVISING THE SERVICES OF THE FOOD COURT AS A SUPPORTING PUBLIC SERVICE - Yuyun Ratnowati , Iva; Devy Pramudiana , Ika; Mustofa, Amirul (International Journal of Multidisciplinary Reseach, 2025)
Public services in hospitals not only consist of medical services, but also include supporting services that play a vital role in ensuring the safety and comfort of service users, such as the food court. The presence of a food court in the hospital area directly affects aspects of health, cleanliness, and public satisfaction, thus requiring maximum supervision from hospital management. This study aims to analyze the management function of Pura Raharja Hospital Surabaya in supervising the food court service as an additional public service, the supervisory methods applied, and the problems encountered in its implementation. This study applies a qualitative approach with a case study design. Information was obtained through in-depth interviews, observation, and document analysis, followed by interactive analysis through data reduction, data presentation, and conclusion drawing. The research findings indicate that hospital management plays a crucial role in supervising food courts through the establishment of internal policies, standard operating procedures, and routine inspections in accordance with health sector regulations. However, effective supervision still faces challenges related to human resources, inter-unit collaboration, and a suboptimal evaluation system. This study highlights the significance of strengthening the management and supervision of non-medical services as an essential component in improving the quality of public services in hospitals.